TRIM25 facilitates mitochondrial dysfunction and extracellular matrix degradation by enhancing USP7‐driven ENO1 deubiquitination during intervertebral disc degeneration - Xiaoming Liu; Wenyu Zhang; Hang Feng; Linying Lai; Chen Cao; Guang Yang; Yanzheng Gao; Bijun Wang; Hui Wang; Bin Yu; Zhenghong Yu (Clinical and Translational Medicine, 2026)
Abstract Background The pathology of intervertebral disc degeneration (IDD) is characterized by metabolic dysregulation within nucleus pulposus (NP) cells. TRIM25 has been implicated in diverse tumors and pathological processes, yet its precise role in mediating mitochondrial function and metabolic alterations during IDD progression remains unclear. Methods Transcriptome sequencing was performed to analyze gene expression changes during IDD progression. Molecular biology techniques including co‐immunoprecipitation and ubiquitination assays were used to investigate the interaction between TRIM25 and the glycolytic enzyme ENO1 and its regulatory mechanism. Cellular and in vivo animal models were employed to validate the effects of the TRIM25‐USP7‐ENO1 axis on glycolysis, mitochondrial function, ATP levels, and extracellular matrix degradation. Results Transcriptome sequencing revealed that glycolysis‐related pathways and TRIM25 were significantly upregulated during IDD progression. Mechanistically, TRIM25 interacted with ENO1. Contrary to its typical E3 ligase function, TRIM25 overexpression stabilized ENO1 by reducing its K48‐linked polyubiquitination. Furthermore, TRIM25 enhanced the interaction between USP7 and ENO1, leading to USP7‐mediated deubiquitination and stabilization of ENO1. Disruption of the TRIM25‐USP7‐ENO1 axis suppressed glycolysis, improved mitochondrial function, elevated ATP levels, and inhibited extracellular matrix degradation. In vivo, modulation of this axis correspondingly accelerated or ameliorated IDD progression. Conclusion We identified a novel TRIM25‐USP7‐ENO1 axis, through which TRIM25 stabilizes ENO1 by promoting USP7‐ENO1 interaction and subsequent USP7‐dependent deubiquitination. This non‐canonical function expands the known role of TRIM25 and highlights a promising therapeutic target for restoring mitochondrial dysfunction and metabolic homeostasis in IDD. Key points TRIM25 recruits the deubiquitinating enzyme USP7 to collaboratively enhance the deubiquitination and stability of the key glycolytic enzyme ENO1, establishing a new regulatory pathway linking inflammation and metabolism. This regulatory axis exacerbates glycolysis, impairs mitochondrial function, disrupts cellular energy homeostasis, and ultimately leads to extracellular matrix degradation, systematically explaining a new pathological mechanism of IDD. Both cellular and animal models confirm that intervention in the TRIM25/USP7/ENO1 axis effectively reverses metabolic imbalance and degenerative progression, offering a promising new therapeutic strategy for IDD. This study extends TRIM25's role from immune regulation to metabolic processes and is the first to report USP7's involvement in glycolytic enzyme regulation, providing a new paradigm for studying “non‐canonical” functions of E3 ligases and deubiquitinating enzymes.